History of studying the kidney pathology in the mirror of numismatics. Report 3. Development of urology - O.V. Syniachenko; M. O. Kolesnyk; N.M. Stepanova; M.V. Iermolaieva (Ukrainian Journal of Nephrology and Dialysis, 2021)
The branch of historical science of numismatics (from the Latin "numisma" - coin) originated in the 19th century and became closely connected with economics, politics, culture and law, it includes a thematic study of coins, medals and plaque. Best of all, the history of uronephrology is illustrated by various forms of the medalist educational art (exonum or paranumismatics), and the medal became the prototype of the memorial coin. This work presents a catalog of more than 400 numismatic materials (including some unique, first cited), reflects the stages of development of the study of the structure and function of the kidneys, methods for diagnosing and treating diseases, there are links to significant historical events, brief biographies of physicians who have made an invaluable contribution are mentioned into the formation of this scientific discipline. The development of urology over 520 years of historical epochs of the New and Modern times were presented, portraits on 60 numismatic materials of well-known specialists-urologists and kidney transplantologists were presented, scientific forums of urologists were reflected on commemorative medals.